IS’ Changing Narrative : How To Counter It - Muhammad Saiful Alam Shah Sudiman (2018)
Despite losing territories, the self-styled Islamic State (IS) continues to remain resilient by reinventing its propaganda. To counter violent extremism proponents should keep themselves abreast of the IS ‘post-territorial defeat narrative’.